Implementasi Metode SAW dan TOPSIS Dalam Sistem Pendukung Keputusan Untuk Seleksi Calon Penegak Saka Bhayangkara - Maulida Syahri Ramadhani Damanik; Suendri; Ali Ikhwan (STMIK Budi Darma, 2024)
Selection of Bhayangkara Saka Enforcer candidates at SMA Negeri 6 Pematangsiantar is done manually in the absence of weighted criteria that have an impact on prospective enforcers who will be selected based on the best abilities and criteria so that the system runs accordingly and efficiently. Prospective enforcers who qualify each year will be sent to participate in Saka Bhayangkara activities so that the selection is carried out annually and the system can be used continuously. So that Decision Support System technology can be applied as a solution. One of the methods that can be used is the SAW and TOPSIS method, this method was chosen because it is simple and easy to apply. The combination of SAW and TOPSIS methods in the decision support system is able to determine the best value from the assessment of 5 criteria with weights determined from the Bhayangkara Saka selection committee. This system can rank the highest to lowest score of each candidate. The accuracy of this system reaches 100% because the final result of the manual calculation matches the system calculation.